El pedagogo en los espacios escolar y no escolar: la ciudadanía en el tránsito - Sheyla Maria Fontenele Macedo; Maribel Machado Oliveira Checcucci (Educa, 2019)
The profession of the pedagogue has delineated in its history a kaleidoscopic profile, given the plurality of roles attributed in the contemporary to this professional, configuring this point in a of the problematics of own identity. The Curriculum Guidelines of the Pedagogy Course (2006) was a document that opened new spaces for labor action and discussions in this field. In this article, we aim to argue about the role of the pedagogue in the sphere of Education for Transit Citizenship, whether in the school or non-school space. The research is qualitative, bibliographical and documentary. This theme opens as an epistemic space full of complexities and challenges for what to do of the pedagogue, especially for greatly expanding the gnosiological about the role that this professional plays in society. From the results, we elucidate that teaching education for citizenship in traffic is still a space that is as an epistemic virgin forest before the nature of the work of the pedagogue. We also reveal that educating for traffic is not the same as education for citizenship, since the term citizenship carries within itself emblematic issues regarding the education of autonomous citizens, sensitive, reflective and participatory, in favor of a humanized society.